2013
DOI: 10.1016/j.appet.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Intersection of identities. Food, role, and the African–American pastor

Abstract: African–American pastors can foster health-related innovations as gatekeepers and advocates within their churches. Personal experiences with food and health likely influence their support of such programs. Identities or meanings attached to societal roles have been shown to motivate individuals’ attitudes and behaviors. Understanding role and eating identities of African–American pastors may have important implications for participation in faith-based health promotion programs. This study aimed to describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…Adult dietary habits and identity both develop over a the course of one's lifetime and their development is interconnected (Bisogni et al, 2002; Devine et al, 1998; Jabs et al, 2000). Based on numerous qualitative studies we believe it is plausible to conceptualize current identity predicting future behavior rather than the reverse (Bisogni et al, 2002; Blake & Bisogni, 2003; Blake et al, 2010; Devine et al, 1999; Harmon et al, 2013), however, future studies should be conducted to examine these relationships. Despite these limitations, this instrument should help researchers better understand how eating identities are related to dietary behaviors, receptivity to diet messages, and response to environments and interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult dietary habits and identity both develop over a the course of one's lifetime and their development is interconnected (Bisogni et al, 2002; Devine et al, 1998; Jabs et al, 2000). Based on numerous qualitative studies we believe it is plausible to conceptualize current identity predicting future behavior rather than the reverse (Bisogni et al, 2002; Blake & Bisogni, 2003; Blake et al, 2010; Devine et al, 1999; Harmon et al, 2013), however, future studies should be conducted to examine these relationships. Despite these limitations, this instrument should help researchers better understand how eating identities are related to dietary behaviors, receptivity to diet messages, and response to environments and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…(Bisogni et al, 2002; Blake & Bisogni, 2003; Blake, Jones, Pringle-Washington, & Ellison, 2010; Devine et al, 1999; Fox & Ward, 2008; Harmon, Blake, Armstead, & Hebert, 2013). Despite awareness of the influence of different types of eating identities on dietary intake, there are currently no valid and reliable instruments available to assess relationships between different combinations of eating identity types and key health behaviors and outcomes, including dietary intake.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them mentioned it directly from the pulpit; but, the CHLs were primarily responsible for making the congregation aware of MPower and encouraging them to maintain enrollment. The literature highlights the importance of pastoral involvement and how it is integral to the success of objectives (Harmon, Blake, Armstead, Hébert, 2013;Hippolyte et al, 2013;Williams et al, 2013;Newlin et al, 2012;De Marco et al, 2011;Austin & Claiborne, 2011;Williams, Glanz, Kegler & Davis, 2009;Ammerman et al, 2003;Markens et al, 2002;Taylor et al, 2000). The experiences of the negative case analysis were directly in line with the literature that suggests pastoral support is integral to successful programming in ecclesiastical establishments.…”
Section: Program Execution Limitations Implementation Barrierssupporting
confidence: 74%
“…A frequently cited catalyst for success in faith-based health promotion is the importance of ministerial endorsement (Harmon, Blake, Armstead, Hébert, 2013;Hippolyte et al, 2013;Williams et al, 2013;Newlin et al, 2012;De Marco et al, 2011;Austin & Claiborne, 2011;Williams, Glanz, Kegler & Davis, 2009;Ammerman et al, 2003;Markens et al, 2002;Taylor et al, 2000). For example, Hippolyte et al(2013), focused on structural components that are integral to program implementation and maintenance within faith-based organizations; this includes but is not limited to the support of a lay leader, appropriate timing of intervention activities, and availability of meeting space.…”
Section: Faith-based Interventions and The African-american Communitymentioning
confidence: 99%
“…98 In other work, we demonstrated that skin color is related to stress, blood pressure, and body mass index, 63 risk factors associated with numerous health outcomes, including cancer. Cultural adaptations, in particular strengthening gender roles in positive modifiable health behaviors 100 and a prominent focus on religion and spirituality, 96,101 provide both ameliorating effects and opportunities for effective intervention. Indeed, other work conducted through the SCCDCN shows the influence of African-American pastors’ food identity 101 on church-level factors related to food/diet and physical activity messaging.…”
Section: Examplesmentioning
confidence: 99%